The Impact of Merdeka Belajar Curriculum on English Language Teaching in International Institute of Business and Tourism. - Kadek Feni Aryati (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to the impact of freedom learning curriculum on English language teaching in International Institute Of Business And Tourism. This research uses descriptive qualitative. Data collection methods are interviews and documentation. Data analysis using data reduction, data display, data verification. research results The Merdeka Belajar curriculum has had a significant impact on English language teaching at the International Business and Tourism Institute. In this context, there are several important points that can be drawn as conclusions. The Merdeka Belajar curriculum has significantly improved English language teaching at the International Business and Tourism Institute by providing flexibility in learning, emphasis on practical skills, use of technology, increased international mobility of students, and improved quality of education. This prepares students to compete in the global business and tourism environment.